تحليل محتوى كتاب العلوم للصف السادس بالمرحلة الابتدائية في ضوء المهارات الحياتية - الشلوي، مريم بنت فراج بن عويض (جامعة حفر الباطن, 2023)
هدفت الدراسة إلى تحليل المهارات الحياتية في محتوى كتاب العلوم للصف السادس بالمرحلة الابتدائية، ولتحقيق أهداف الدراسة صممت الباحثة أداة الدراسة، التي تمثلت في بطاقة تحليل المحتوى، وتضمنت قائمة بعدد من المهارات الحياتية التي يندرج تحتها عدد من المؤشرات تقيس تلك المهارات، وقد اعتمدت الدراسة على المنهج الوصفي التحليلي القائم على تحليل المحتوى، لتحليل محتوى كتاب العلوم للصف السادس للمرحلة الابتدائية في المملكة العربية السعودية بما يتضمنه من المهارات الحياتية. وأظهرت نتائج الدراسة أن كتاب العلوم للصف السادس الابتدائي بفصله الأول كان أكثر اهتمامًا بالمهارات الحياتية من الفصل الثاني، وأن كتاب العلوم للصف السادس الابتدائي بالفصلين الأول والثاني جمع (102) تكرارًا للمهارات الحياتية، توزعت على (7) مهارات، وقد حصلت مهارة التفكير الناقد على أعلى نسبة مئوية (25.20%)، وتبعها بأعلى نسبة مهارة الملاحظة (22.9%)، وحصلت المهارات الصحية على أقل نسبة مئوية بلغت (5.5%). ودلّت النتائج على أن مهارة التفكير الناقد هي الأكثر توافرًا في كتاب العلوم للصف السادس الابتدائي، بعدد (35) مرة، وكانت المهارات الصحية هي الأقل توافرًا بعدد (6) مرات. وكانت مهارات التفكير الناقد الأكثر تضمينا في كتاب العلوم للصف السادس، وبشكل خاص في الفصل الأول، وحازت المهارات البيئية على المرتبة الأولى من خلال التحليل. وفي ضوء النتائج التي أشارت إليها الدراسة؛ أوصت الباحثة بتضمين المهارات البيئية والصحية والتحليل في كتاب العلوم للصف السادس بالمرحلة الابتدائية، ومراعاة التوازن في توظيف المهارات الحياتية بمنهاج العلوم بشكل عام للمرحلة الابتدائية، وكتاب العلوم للصف السادس بشكل خاص. The research aimed to analyze the life skills in the content of the science book for the sixth grade in the primary stage, and to achieve the research objectives, the researcher designed the research tool, which was the content analysis card, and included a list of a number of life skills under which a number of indicators that measure these skills fall, The research relied on the descriptive analytical approach based on content analysis, to analyze the content of the science book for the sixth grade of the primary stage in the Kingdom of Saudi Arabia, including life skills. The results of the research showed that the science book for the sixth grade of primary school in its first semester was more interested in life skills than the second semester, and that the science book for the sixth grade of primary school in the first and second semesters collected (102) repetitions of life skills, distributed into (7) skills, and the critical thinking skill got a The highest percentage was (20.25%), followed by the highest percentage of observation skill (9.22%), and health skills got the lowest percentage (5.5%). The results indicated that the critical thinking skill is the most available in the science book for the sixth grade of primary school, with a number of (35) times, and health skills were the least available, with a number of (6) times. Critical thinking skills were the most included in the sixth-grade science book, especially in the first semester, and environmental skills ranked first through analysis .In light of the results indicated by the study; The researcher recommended Paying attention to including environmental and health skills and analysis in the science book for the sixth grade in the primary stage.Taking into account the balance in employing life skills in the science curriculum in general for the primary stage, and the science textbook for the sixth grade in particular .
Keywords: التعليم الابتدائي -- المناهج الدراسية -- مادة العلوم -- المهارات الحياتية -- تحليل المحتوي